Austenitic alloy

JP7939610B2Pending Publication Date: 2026-10-22NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2026506032
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-11-15
Filing Date
2025-10-24
Publication Date
2026-10-22
Estimated Expiration
2045-10-24

AI Technical Summary

Benefits of technology

【0013】 本開示のオーステナイト合金材では、次世代型地熱環境においても優れた耐食性が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939610000004
    Figure 0007939610000004
  • Figure 0007939610000001
    Figure 0007939610000001
  • Figure 0007939610000002
    Figure 0007939610000002
Patent Text Reader

Abstract

An austenitic alloy material according to the present disclosure has a chemical composition that contains, in mass%, more than 0% but not more than 0.020% of C, 0.02-0.80% of Si, 0.10-1.00% of Mn, more than 0% but not more than 0.030% of P, more than 0% but not more than 0.0015% of S, 16.00-28.00% of Ni, 0.01-1.00% of Co, not less than 19.00% but less than 21.00% of Cr, 3.00-9.00% of Mo, 0.150-0.250% of N, 0.005-0.200% of sol. Al, more than 0% but not more than 0.0150% of O, 0.0005-0.0100% of Ca, 0-0.50% of Cu, and 0-3.00% of W, with the balance being made up of Fe and impurities. The austenitic alloy material satisfies formula (1), and has a dislocation density of 1.0 × 1014 m-2 or more. (1): Mo / Ni ≥ 0.20 In formula (1), the content in mass% of the corresponding element is substituted for each element symbol.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present disclosure relates to an alloy material, and more specifically, relates to an austenitic alloy material whose microstructure is composed of austenite.

BACKGROUND ART

[0002] As one type of clean energy, geothermal power generation has attracted attention. Geothermal power generation has almost zero CO2 emissions, is not affected by natural conditions such as weather, and enables stable power generation. In conventional geothermal power generation, a production well is drilled into a geothermal reservoir, which is an underground reservoir of hot water and steam, and power is generated using naturally erupting steam. However, depending on the geothermal reservoir, the amounts of hot water and steam in the geothermal reservoir may become insufficient over time. In this case, the power generation output decreases.

[0003] Accordingly, to solve such problems, the following next-generation geothermal power generation has recently been proposed. The next-generation geothermal power generation utilizes a geothermal reservoir at a position deeper than the geothermal reservoir used in conventional geothermal power generation, thereby utilizing hot water and steam at a high temperature of 300°C or higher. Therefore, the power generation efficiency can be improved compared with conventional geothermal power generation. The next-generation geothermal power generation particularly aims to realize supercritical geothermal power generation that utilizes hot water, steam or supercritical fluid exceeding 374°C.

[0004] The above-described next-generation geothermal power generation utilizes a geothermal reservoir deeper underground than the geothermal reservoir used in conventional geothermal power generation. Therefore, the geothermal reservoir for next-generation geothermal power generation is in a corrosive environment with a high temperature of about 300 to 500°C, containing corrosive substances represented by H2S and having a low pH. Such a high-temperature and acidic environment at about 300 to 500°C is referred to as "next-generation geothermal environment" in the present specification. Alloy materials used for production wells in such a next-generation geothermal environment are required to have excellent corrosion resistance.

[0005] Alloy materials for geothermal power generation applications are proposed in International Publication No. 2021 / 256128 (Patent Document 1) and International Publication No. 2001 / 090432 (Patent Document 2).

[0006] The alloy material disclosed in Patent Document 1 has a chemical composition containing, by mass%, Cr: 11.5-35.0%, Ni: 23.0-60.0%, and Mo: 0.5-17.0%, and has an austenite phase as its microstructure, with the Mo concentration (by mass%) at the grain boundaries of the austenite phase being 4.0 times or less than the Mo concentration (by mass%) within the austenite grains. In this alloy material, the difference in Mo concentration between the grain boundaries and within the austenite crystal grains is reduced. As a result, corrosion resistance can be maintained, as stated in Patent Document 1.

[0007] The austenitic alloy material disclosed in Patent Document 2 consists of, by mass%, Cr: 23-30%, Ni: 25-35%, Mo: 3-6%, Mn: 1-6%, N: 0-0.40%, C: 0.05% or less, Si: 1.0% or less, S: 0.02% or less, Cu: 3.0% or less, and the remainder being iron and impurities. Patent Document 2 states that this austenitic alloy material, having the above chemical composition, provides excellent corrosion resistance. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] International Publication No. 2021 / 256128 [Patent Document 2] International Publication No. 2001 / 090432 [Non-patent literature]

[0009] [Non-Patent Document 1] HMRietveld, "A Profile Refinement Method for Nuclear and Magnetic Structures", Journal of Applied Crystallography, 1969, Volume 2, p.65-71 [Overview of the Initiative] [Problems that the invention aims to solve]

[0010] However, Patent Documents 1 and 2 do not consider corrosion resistance in the context of next-generation geothermal environments.

[0011] The purpose of this disclosure is to provide an austenitic alloy material that exhibits excellent corrosion resistance even in next-generation geothermal environments. [Means for solving the problem]

[0012] The austenitic alloy material disclosed herein has a chemical composition in mass percent of: C: greater than 0% and less than or equal to 0.020%, Si: 0.02 to 0.80%, Mn: 0.10 to 1.00%, P: greater than 0% and less than or equal to 0.030%, S: greater than 0% and less than or equal to 0.0015%, Ni: 16.00 to 28.00%, Co: 0.01 to 1.00%, Cr: 19.00 to 21.00%. The composition is less than 0%, consisting of Mo: 3.00-9.00%, N: 0.150-0.250%, sol.Al: 0.005-0.200%, O: greater than 0% and less than or equal to 0.0150%, Ca: 0.0005-0.0100%, Cu: 0-0.50%, W: 0-3.00%, and the remainder being Fe and impurities, satisfying formula (1), and having a rearrangement density of 1.0 × 10⁻⁶. 14 m -2 That's all. Mo / Ni≧0.20 (1) Here, the elemental symbols in equation (1) are substituted with the mass percentage content of the corresponding element. [Effects of the Invention]

[0013] The austenitic alloy material disclosed herein provides excellent corrosion resistance even in next-generation geothermal environments. [Brief explanation of the drawing]

[0014] [Figure 1] Figure 1 is a graph showing the relationship between Mo / Ni and the corrosion rate (g·m-2·h-1), which is an indicator of corrosion resistance, for an austenitic alloy material that satisfies the chemical composition of this embodiment and has a dislocation density of 1.0 × 10¹⁴ m-2 or higher. [Modes for carrying out the invention]

[0015] The inventors investigated alloy materials that can obtain excellent corrosion resistance even in next-generation geothermal environments, which are corrosive environments of about 300 to 500°C, from the perspective of chemical composition. In high-temperature corrosive environments such as next-generation geothermal environments, it is thought that not only Cr but also Mo contributes to improving corrosion resistance. In next-generation geothermal environments, Mo forms a sulfide film on the surface of the alloy material. This sulfide film enhances the corrosion resistance of the alloy material. Therefore, it is thought that by increasing the Mo content in addition to the Cr content, corrosion resistance in next-generation geothermal environments can be improved. Furthermore, Co reduces the corrosion rate of alloy materials in next-generation geothermal environments.

[0016] Based on the above considerations, the inventors investigated alloy materials suitable for use in next-generation geothermal environments from the perspective of chemical composition. As a result, in mass%, C: greater than 0% and less than or equal to 0.020%, Si: 0.02 to 0.80%, Mn: 0.10 to 1.00%, P: greater than 0% and less than or equal to 0.030%, S: greater than 0% and less than or equal to 0.0015%, Ni: 16.00 to 28.00%, Co: 0.01 to 1.00%, Cr: less than 19.00 to 21.00%, Mo: 3.00 to 9.00%, N: 0.150 to 0.25% The inventors believe that an austenitic alloy material having a chemical composition consisting of 0%, sol.Al:0.005~0.200%, O:greater than 0% and less than or equal to 0.0150%, Ca:0.0005~0.0100%, Cu:0~0.50%, W:0~3.00%, and the remainder being Fe and impurities, may be able to obtain excellent corrosion resistance even in next-generation geothermal environments.

[0017] The inventors further investigated means of improving the corrosion resistance of an austenitic alloy material having the above-mentioned chemical composition in next-generation geothermal environments from the viewpoint of microstructure.

[0018] As described above, in order to increase the Mo content to 3.00-9.00% and enhance corrosion resistance through the action of Mo, it is effective to facilitate the diffusion of Mo to the surface layer of the austenitic alloy material in next-generation geothermal environments. Here, the inventors considered that dislocations in the austenitic alloy material function as diffusion paths for Mo. Specifically, by increasing the dislocation density in the austenitic alloy material, Mo can more easily diffuse to the surface layer via dislocations in next-generation geothermal environments. As a result, a stable sulfide film of Mo is formed on the surface of the austenitic alloy material, improving corrosion resistance in next-generation geothermal environments.

[0019] Based on the above considerations, the inventors investigated and examined the relationship between the dislocation density of an austenitic alloy material having the above-mentioned chemical composition and its corrosion resistance in a next-generation geothermal environment. As a result, in an austenitic alloy material having the above-mentioned chemical composition, a dislocation density of 1.0 × 10⁻⁶ 14 m -2 The above results indicate that corrosion resistance will be enhanced even in next-generation geothermal environments.

[0020] However, having the above chemical composition and a rearrangement density of 1.0 × 10⁻⁶ 14 m -2 Even with the austenitic alloy materials described above, excellent corrosion resistance in next-generation geothermal environments was still sometimes not achieved. Therefore, the inventors conducted further investigations and studies. As a result, the inventors obtained the following new findings.

[0021] In high-temperature corrosive environments such as next-generation geothermal environments, if the Ni and Mo content in austenitic alloy materials is high, Ni inhibits the diffusion of Mo. On the other hand, Ni is an element necessary to enhance stress corrosion cracking resistance, and if the Ni content is reduced to less than 16.00%, sufficient stress corrosion cracking resistance in next-generation geothermal environments cannot be obtained. Therefore, the inventors considered that if the Ni content is maintained in the above chemical composition, and the ratio of Mo content to Ni content (=Mo / Ni) is further increased, Mo will diffuse more easily in next-generation geothermal environments.

[0022] Based on the above findings, the present inventors, for austenitic alloy materials that satisfy the aforementioned chemical composition and have a dislocation density of 1.0×10 14 m -2 or more, further investigated the relationship between the ratio of Mo content to Ni content and the corrosion resistance in next-generation geothermal environments.

[0023] Figure 1 shows an austenitic alloy material that satisfies the aforementioned chemical composition and has a dislocation density of 1.0×10 14 m -2 or more, and is a graph showing the relationship between Mo / Ni and the corrosion rate (g·m, which is an indicator of corrosion resistance) -2 ·h -1 ). Figure 1 was created based on the results of Examples described later.

[0024] Referring to Figure 1, when Mo / Ni is less than 0.20, the corrosion rate does not change much even if Mo / Ni increases. On the other hand, when Mo / Ni is 0.20 or more, as Mo / Ni increases, the corrosion rate decreases remarkably to 0.100g·m -2 ·h -1 or less. That is, in the curve C1 of Figure 1, an inflection point exists in the vicinity of Mo / Ni=0.20. Therefore, if the aforementioned chemical composition is satisfied, the dislocation density is set to 1.0×10 14 m -2 or more, and Mo / Ni is further set to 0.20 or more, excellent corrosion resistance can be obtained even in a next-generation geothermal environment.

[0025] The austenitic alloy material of the present embodiment completed based on the above findings has the following configuration.

[0026] The first form of austenitic alloy material has a chemical composition in mass percent of: C: greater than 0% and less than or equal to 0.020%, Si: 0.02-0.80%, Mn: 0.10-1.00%, P: greater than 0% and less than or equal to 0.030%, S: greater than 0% and less than or equal to 0.0015%, Ni: 16.00-28.00%, Co: 0.01-1.00%, Cr: 19.00-21.00%. The composition is less than %, consisting of Mo: 3.00-9.00%, N: 0.150-0.250%, sol.Al: 0.005-0.200%, O: greater than 0% and less than or equal to 0.0150%, Ca: 0.0005-0.0100%, Cu: 0-0.50%, W: 0-3.00%, and the remainder being Fe and impurities, satisfying formula (1), and having a rearrangement density of 1.0 × 10⁻⁶. 14 m -2 That's all. Mo / Ni≧0.20 (1) Here, the elemental symbols in equation (1) are substituted with the mass percentage content of the corresponding element.

[0027] The second form of the austenitic alloy material is the first form of the austenitic alloy material, and its chemical composition contains one or more elements selected from the group consisting of Cu: 0.01 to 0.50% and W: 0.01 to 3.00% by mass.

[0028] The third form of austenitic alloy material is the first or second form of austenitic alloy material, and its chemical composition contains, by mass%, W: 0.10 to 3.00%.

[0029] The fourth form of austenitic alloy material is an austenitic alloy material of any one of the first to third forms, and is an alloy tube.

[0030] The austenitic alloy material of this embodiment will be described in detail below. Unless otherwise specified, the "%" for elements refers to mass percentage. In the following description, the austenitic alloy material will also be simply referred to as the "alloy material".

[0031] [Characteristics of the austenitic alloy material of this embodiment] The austenitic alloy material of this embodiment satisfies the following features 1 to 3. (Feature 1) The chemical composition, in mass%, consists of: C: greater than 0% and less than or equal to 0.020%, Si: 0.02-0.80%, Mn: 0.10-1.00%, P: greater than 0% and less than or equal to 0.030%, S: greater than 0% and less than or equal to 0.0015%, Ni: 16.00-28.00%, Co: 0.01-1.00%, Cr: less than 19.00-21.00%, Mo: 3.00-9.00%, N: 0.150-0.250%, sol.Al: 0.005-0.200%, O: greater than 0% and less than or equal to 0.0150%, Ca: 0.0005-0.0100%, Cu: 0-0.50%, W: 0-3.00%, and the remainder being Fe and impurities. (Feature 2) The chemical composition satisfies formula (1). Mo / Ni≧0.20 (1) Here, the elemental symbols in equation (1) are substituted with the mass percentage content of the corresponding element. (Feature 3) Dislocation density is 1.0 × 10 14 m -2 That's all. Features 1 to 3 are explained below.

[0032] [(Feature 1) Regarding chemical composition] The chemical composition of the austenitic alloy material in this embodiment contains the following elements:

[0033] C: More than 0% and less than 0.020% Carbon (C) stabilizes austenite. Even a small amount of C is sufficient to achieve the above effect to some extent. However, if the carbon content exceeds 0.020%, chromium carbides will form at the grain boundaries. The formation of chromium carbides creates chromium-deficient regions with low chromium content within the alloy. Therefore, even if the content of other elements is within the range of this embodiment, the corrosion resistance of the alloy in next-generation geothermal environments will decrease. Therefore, the C content is greater than 0% and less than or equal to 0.020%. The preferred lower limit of the C content is 0.001%, more preferably 0.003%, more preferably 0.004%, more preferably 0.006%, and more preferably 0.008%. The preferred upper limit for the C content is 0.018%, more preferably 0.016%, and even more preferably 0.014%.

[0034] Si: 0.02~0.80% Silicon (Si) deoxidizes alloys in the steelmaking process. If the Si content is less than 0.02%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Si content exceeds 0.80%, the hot workability of the alloy material will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Si content is 0.02-0.80%. The preferred lower limit for the Si content is 0.05%, more preferably 0.08%, and even more preferably 0.10%. The preferred upper limit for the Si content is 0.70%, more preferably 0.60%, even more preferably 0.55%, and even more preferably 0.50%.

[0035] Mn: 0.10~1.00% Manganese (Mn) deoxidizes and desulfurizes alloys in the steelmaking process. Mn also stabilizes austenite. If the Mn content is less than 0.10%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Mn content exceeds 1.00%, the hot workability of the alloy material will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Mn content is 0.10-1.00%. The preferred lower limit of the Mn content is 0.15%, more preferably 0.20%, even more preferably 0.30%, and even more preferably 0.40%. The preferred upper limit for the Mn content is 0.90%, more preferably 0.80%, more preferably 0.70%, more preferably 0.65%, and still more preferably 0.60%.

[0036] P: More than 0% and less than 0.030% Phosphorus (P) is an unavoidable impurity. That is, the P content is greater than 0%. If the P content exceeds 0.030%, P will excessively segregate at the grain boundaries. In this case, even if the content of other elements is within the range of this embodiment, the corrosion resistance of the alloy material in next-generation geothermal environments will decrease. Therefore, the P content is greater than 0% and less than or equal to 0.030%. A low phosphorus (P) content is preferable. However, excessive reduction of the P content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the P content is 0.001%, more preferably 0.002%, and even more preferably 0.003%. The preferred upper limit for the P content is 0.028%, more preferably 0.026%, even more preferably 0.020%, and even more preferably 0.015%.

[0037] S: More than 0% and less than 0.0015% Sulfur (S) is an unavoidable impurity. That is, the S content is greater than 0%. If the S content exceeds 0.0015%, S will combine with Mn to produce excess MnS. In this case, even if the content of other elements is within the range of this embodiment, the pitting corrosion resistance of the alloy material will decrease. Therefore, the sulfur content is greater than 0% and less than or equal to 0.0015%. A low sulfur (S) content is preferable. However, excessive reduction of the S content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the S content is 0.0001%, more preferably 0.0002%, and even more preferably 0.0003%. The preferred upper limit for the S content is 0.0012%, more preferably 0.0010%, and even more preferably 0.0008%.

[0038] Ni: 16.00~28.00% Nickel (Ni) stabilizes austenite, increasing its high-temperature strength in next-generation geothermal environments. Ni further enhances stress corrosion cracking resistance in next-generation geothermal environments. If the Ni content is less than 16.00%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Ni content exceeds 28.00%, the above effect saturates. Furthermore, manufacturing costs increase. Therefore, the Ni content is 16.00-28.00%. The preferred lower limit of the Ni content is 16.50%, more preferably 17.00%, more preferably 17.30%, more preferably 17.50%, more preferably 18.00%, and more preferably 18.50%. The preferred upper limit for the Ni content is 27.50%, more preferably 27.00%, even more preferably 26.00%, and even more preferably 25.00%.

[0039] Co: 0.01~1.00% Cobalt (Co) stabilizes austenite, increasing its high-temperature strength in next-generation geothermal environments. Furthermore, Co reduces the corrosion rate of alloy materials in next-generation geothermal environments. If the Co content is less than 0.01%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the CO content exceeds 1.00%, manufacturing costs increase significantly. Therefore, the Co content is 0.01-1.00%. The preferred lower limit of the Co content is 0.02%, more preferably 0.03%, more preferably 0.05%, more preferably 0.08%, and more preferably 0.10%. The preferred upper limit for the Co content is 0.90%, more preferably 0.80%, more preferably 0.70%, more preferably 0.50%, and more preferably 0.20%.

[0040] Cr: 19.00-21.00% Chromium (Cr) forms a passivation film, enhancing the corrosion resistance of alloy materials in next-generation geothermal environments. If the Cr content is less than 19.00%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Cr content is 21.00% or more, the hot workability of the alloy material will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Cr content is less than 19.00-21.00%. The preferred lower limit for the Cr content is 19.10%, more preferably 19.20%, more preferably 19.25%, more preferably 19.30%, and more preferably 19.40%. The preferred upper limit for the Cr content is 20.90%, more preferably 20.80%, more preferably 20.70%, and still more preferably 20.60%.

[0041] Mo: 3.00~9.00% Molybdenum (Mo) forms a sulfide film on the surface of alloy materials in next-generation geothermal environments. This enhances the corrosion resistance of alloy materials in next-generation geothermal environments. If the Mo content is less than 3.00%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Mo content exceeds 9.00%, the hot workability of the alloy material will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the Mo content is 3.00-9.00%. The preferred lower limit of the Mo content is 3.10%, more preferably 3.20%, more preferably 3.30%, more preferably 3.50%, more preferably 4.00%, and more preferably 4.50%. The preferred upper limit for the Mo content is 8.90%, more preferably 8.80%, more preferably 8.50%, more preferably 8.00%, more preferably 7.50%, and more preferably 7.10%.

[0042] N: 0.150~0.250% Nitrogen (N) dissolves in the alloy material to stabilize the austenite. Solid-solution N further enhances the high-temperature strength of the alloy material in next-generation geothermal environments. If the N content is less than 0.150%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the N content exceeds 0.250%, the hot workability of the alloy material will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the N content is 0.150-0.250%. The preferred lower limit of the N content is 0.160%, more preferably 0.170%, more preferably 0.180%, and still more preferably 0.190%. The preferred upper limit for the N content is 0.240%, more preferably 0.230%, and even more preferably 0.220%.

[0043] sol.Al: 0.005~0.200% Aluminum (Al) deoxidizes alloys in the steelmaking process. Furthermore, Al enhances the oxidation resistance of alloy materials in next-generation geothermal environments. If the Al content is less than 0.005%, the above effects cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Al content exceeds 0.200%, coarse oxides are formed. In this case, even if the content of other elements is within the range of this embodiment, the cleanliness of the alloy material decreases. As a result, the hot workability of the alloy material decreases. Therefore, the sol.Al content is between 0.005% and 0.200%. The preferred lower limit for the sol.Al content is 0.010%, more preferably 0.015%, and even more preferably 0.020%. The preferred upper limit for the sol.Al content is 0.150%, more preferably 0.120%, more preferably 0.100%, more preferably 0.080%, more preferably 0.050%, more preferably 0.030%, and more preferably 0.025%. Note that the sol.Al content refers to the content (mass %) of acid-soluble Al (sol.Al).

[0044] O: More than 0% and less than 0.0150% Oxygen (O) is an unavoidable impurity. In other words, the O content is greater than 0%. If the O content exceeds 0.0150%, an excess of oxides will be formed. In this case, even if the content of other elements is within the range of this embodiment, the cleanliness of the alloy material will decrease. Consequently, the hot workability of the alloy material will decrease. Therefore, the O content is greater than 0% and less than or equal to 0.0150%. A low oxygen content is preferable. However, excessive reduction of the oxygen content increases manufacturing costs. Therefore, considering normal industrial production, the preferred lower limit of the oxygen content is 0.0001%, more preferably 0.0005%, and even more preferably 0.0010%. The preferred upper limit for the O content is 0.0085%, more preferably 0.0065%, and even more preferably 0.0045%.

[0045] Ca: 0.0005~0.0100% Calcium (Ca) fixes oxygen (O) and sulfur (S) as inclusions, improving the hot workability of the alloy material. If the Ca content is less than 0.0005%, the above effect cannot be fully obtained, even if the content of other elements is within the range of this embodiment. On the other hand, if the Ca content exceeds 0.0100%, the cleanliness of the alloy material decreases. Therefore, even if the content of other elements is within the range of this embodiment, the hot workability of the alloy material decreases. Therefore, the Ca content is between 0.0005% and 0.0100%. The preferred lower limit for the Ca content is 0.0010%, more preferably 0.0015%, and even more preferably 0.0020%. The preferred upper limit for the Ca content is 0.0090%, more preferably 0.0080%, more preferably 0.0075%, more preferably 0.0065%, more preferably 0.0055%, and more preferably 0.0045%.

[0046] The remainder of the chemical composition of the austenitic alloy material in this embodiment consists of Fe and impurities. Here, impurities refer to substances that are introduced during the industrial production of the austenitic alloy material from raw materials such as ore, scrap, or the manufacturing environment, and are acceptable within a range that does not adversely affect the austenitic alloy material in this embodiment.

[0047] [About Optional Elements] The chemical composition of the austenitic alloy material in this embodiment may further contain, in place of some of the Fe, one or more elements selected from the group consisting of Cu: 0-0.50% and W: 0-3.00%. These elements are all optional and enhance the corrosion resistance of the alloy material in next-generation geothermal environments. These optional elements will be described below.

[0048] Cu: 0~0.50% Copper (Cu) is an optional element and does not need to be included. In other words, the Cu content may be 0%. When copper (Cu) is present, that is, when the Cu content is greater than 0%, the Cu enhances the corrosion resistance of the alloy material in next-generation geothermal environments. Even a small amount of Cu can provide some degree of the above effect. However, if the Cu content exceeds 0.50%, even if the content of other elements is within the range of this embodiment, the corrosion resistance of the alloy material in next-generation geothermal environments will actually decrease. Therefore, the copper content is 0-0.50%. The preferred lower limit for the Cu content is 0.01%, more preferably 0.10%, and even more preferably 0.15%. The preferred upper limit for the Cu content is 0.47%, more preferably 0.45%, even more preferably 0.40%, and even more preferably 0.35%.

[0049] W: 0~3.00% Tungsten (W) is an optional element and does not need to be included. In other words, the W content may be 0%. When W is present, that is, when the W content is greater than 0%, W enhances the corrosion resistance of alloy materials in next-generation geothermal environments. Even a small amount of W will provide some degree of the above effect. However, if the W content exceeds 3.00%, the hot workability of the alloy material will decrease, even if the content of other elements is within the range of this embodiment. Therefore, the W content is 0-3.00%. The preferred lower limit of the W content is 0.01%, more preferably 0.05%, even more preferably 0.10%, and even more preferably 0.12%. As will be described later, in the austenitic alloy material of this embodiment, if features 1 to 3 are satisfied, and the W content is 0.10% or more, the corrosion resistance is significantly improved. The preferred upper limit for the W content is 2.50%, more preferably 2.00%, even more preferably 1.50%, and even more preferably 1.00%.

[0050] [Regarding (Feature 2) Equation (1)] Assuming that the austenitic alloy material of this embodiment satisfies Feature 1, it also satisfies the following formula (1). Mo / Ni≧0.20 (1) Here, the elemental symbols in equation (1) are substituted with the mass percentage content of the corresponding element.

[0051] F1 is defined as follows: F1 = Mo / Ni F1 is an index indicating the ease of Mo diffusion in next-generation geothermal environments. In high-temperature corrosive environments such as next-generation geothermal environments, if an austenitic alloy material has a chemical composition that satisfies characteristic 1, Mo diffusion is easily inhibited by Ni. If F1 is 0.20 or higher, the inhibition of Mo diffusion by Ni in next-generation geothermal environments can be suppressed. As a result, Mo can easily diffuse onto the surface of the alloy material. Consequently, as shown in Figure 1, the corrosion rate in next-generation geothermal environments can be sufficiently suppressed, and excellent corrosion resistance can be obtained.

[0052] Specifically, referring to Figure 1, when Mo / Ni is less than 0.20, the corrosion rate does not change significantly even if Mo / Ni increases. On the other hand, when Mo / Ni is 0.20 or higher, as Mo / Ni increases, the corrosion rate decreases significantly, and the corrosion resistance increases significantly. In other words, in curve C1 in Figure 1, there is an inflection point near Mo / Ni = 0.20. If F1 is 0.20 or higher, assuming that features 1 and 3 are satisfied, the corrosion rate obtained by the method described in [Method for Evaluating Corrosion Resistance] below is 0.100 g·m -2 ·h -1 The following can be done:

[0053] The preferred lower limit for F1 is 0.25. In this case, as shown in Figure 1, which was created based on the examples described later, the corrosion rate is 0.080 g·m -2 ·h -1 The following is possible. A more preferable lower limit for F1 is 0.30. In this case, the corrosion rate is 0.040 g·m -2 ·h -1 The following is possible. A more preferable lower limit for F1 is 0.35.

[0054] In Figure 1, plots labeled 9, 10, and 22 correspond to test numbers 9, 10, and 22 in the examples described later, respectively. The austenitic alloy materials for these test numbers contain 0.10% or more W by mass. Curve C2 in Figure 1 is composed of plots 9, 10, and 22, which contain 0.10% or more W. On the other hand, curve C1 in Figure 1 is composed of plots with a W content of less than 0.10%. Referring to curves C1 and C2, the corrosion rate in curve C2, where the W content is 0.10% or more, is significantly lower compared to curve C1, where the W content is less than 0.10%. Therefore, in the austenitic alloy material of this embodiment, if features 1 and 3 are satisfied, F1 is 0.20 or more (feature 2), and the W content is 0.10% or more, corrosion resistance can be significantly improved. There is no particular upper limit to F1, but if the alloy material satisfies characteristic 1, the upper limit of F1 is 0.56. Note that F1 is the value obtained by rounding the third decimal place of the obtained value to the second decimal place.

[0055] [(Feature 3) Regarding dislocation density] In the austenitic alloy material of this embodiment, the dislocation density is 1.0 × 10⁻⁶. 14 m -2 That's all. Dislocations function as diffusion paths for Mo to diffuse from the interior to the surface of alloy materials in next-generation geothermal environments. Dislocation density is 1.0 × 10⁻⁶ 14 m -2 If the value is less than [value missing], the amount of diffusion paths in the alloy material is insufficient. Therefore, in this case, even if the austenitic alloy material satisfies features 1 and 2, a sufficient amount of Mo will not diffuse to the surface of the alloy material in the next-generation geothermal environment. As a result, excellent corrosion resistance in the next-generation geothermal environment cannot be obtained.

[0056] Dislocation density is 1.0 × 10 14 m -2 If the above conditions are met, a sufficient amount of Mo diffusion paths are present in the alloy material. Therefore, assuming that features 1 and 2 are satisfied, excellent corrosion resistance can be obtained in next-generation geothermal environments.

[0057] The preferred lower limit of dislocation density is 1.1 × 10⁻⁶. 14 m -2 And more preferably 1.2 × 10 14 m -2 And more preferably 1.3 × 10 14 m -2 And more preferably 1.5 × 10 14 m -2 And more preferably 2.0 × 10 14 m -2 That is the case. There is no particular upper limit to the dislocation density. For example, the upper limit of the dislocation density could be 100.0 × 10⁻⁶. 14 m -2 For example, 10.0 × 10 14 m -2 For example, 5.0 × 10 14 m -2 That is the case.

[0058] [Method for measuring dislocation density] Dislocation density is measured by the following method: A test specimen is taken from an austenitic alloy material. If the alloy material is an alloy tube, the test specimen is taken from the center of the wall thickness. The size of the test specimen is, for example, 20 mm wide, 20 mm long, and 2 mm thick. The thickness direction of the test specimen is in the direction of the tube diameter. The length direction of the test specimen is in the direction of the tube axis. The surface with a width of 20 mm and a length of 20 mm is used as the measurement surface. If the alloy material is an alloy sheet, the test specimen is taken from the center of the sheet thickness. The size of the test specimen is, for example, 20 mm wide, 20 mm long, and 2 mm thick. The thickness direction of the test specimen is the sheet thickness direction. The length direction of the test specimen is the rolling direction. The surface with a width of 20 mm and a length of 20 mm is used as the measurement surface. If the alloy material is a round bar, the test specimen is taken from the R / 2 position. Here, the R / 2 position refers to the center position of radius R in a cross section perpendicular to the longitudinal direction of the round bar. The size of the test specimen is, for example, 20 mm in width, 20 mm in length, and 2 mm in thickness. The thickness direction of the test specimen is the radial direction of the round bar. The length direction of the test specimen is the axial direction. The surface with a width of 20 mm and a length of 20 mm is used as the measurement surface.

[0059] The measurement surface of the collected test specimen is polished to a mirror finish. After mirror polishing, the measurement surface is electropolished using an electrolytic solution containing 10% by volume of perchloric acid with acetic acid as the solvent to remove strain from the surface of the test specimen.

[0060] X-ray diffraction (XRD) profiles are measured on the measurement surface after electropolishing. For X-ray diffraction, a Co tube is used as the cathode, and the X-ray source is CoKα. The acceleration voltage is set to 40kV, and the acceleration current to 40mA. The θ-2θ method is employed for profiling. The scan range is 40-130° at 2θ. The X-ray diffractometer used is, for example, the Rint-2500 manufactured by Rigaku Corporation.

[0061] The obtained X-ray diffraction profiles are analyzed, and the diffraction of the {111}, {220}, and {311} planes of the FCC crystal structure is fitted using the Rietveld method described in Non-Patent Literature 1 to obtain the full width at half maximum (FWHM) ΔK. For the measurement of the X-ray profile originating from the X-ray diffractometer, an austenitic alloy material that satisfies Feature 1 and is considered to have an extremely low dislocation density, which has been solution-treated at 1180°C (an austenitic alloy material that satisfies Feature 1), is used.

[0062] Based on the full width at half maximum ΔK obtained by the method described above and the Williamson-Hall equation (A), the heterogeneous strain ε of the specimen is determined. ΔK×cosθ / λ=0.9 / D+2ε×sinθ / λ (A) Here, in equation (A), θ represents the diffraction angle, λ represents the wavelength of the X-ray (m), and D represents the grain size (m). Specifically, the data plotted with ΔK × cosθ / λ on the vertical axis and 2 × sinθ / λ on the horizontal axis is approximated by a linear equation, and the resulting slope ε is defined as the heterogeneous strain ε.

[0063] Furthermore, using the obtained heterogeneous strain ε and equation (B), the dislocation density ρ(m -2 ) ρ = 14.4 × ε 2 / b 2 (B) Here, in equation (B), b is the Burgers vector of the FCC crystal structure (b = 0.2545 × 10⁻¹⁵). -9 Substitute (m) into the equation. Note that the dislocation density ρ is expressed as a floating-point number consisting of a mantissa, base, and exponent, based on the value obtained from equation (B). In this case, the base is 10 and the exponent is 14. Furthermore, the value of the mantissa is rounded to the first decimal place.

[0064] [Effects of the austenitic alloy material in this embodiment] The austenitic alloy material of this embodiment satisfies features 1 to 3. Therefore, excellent corrosion resistance can be obtained in next-generation geothermal environments.

[0065] [Method for evaluating corrosion resistance] The corrosion resistance of the austenitic alloy material in this embodiment is evaluated by the following method.

[0066] A test specimen is taken from an austenitic alloy material. If the alloy material is an alloy tube, the test specimen is taken from the center of the wall thickness. The size of the test specimen is, for example, 20 mm in length, 10 mm in width, and 3 mm in thickness. A through hole with a diameter of 5 mm extending in the thickness direction is made at the longitudinal end of the test specimen. The through hole is formed to set the test specimen in a suspended state inside the autoclave, as described later. The thickness direction of the test specimen is the diameter direction of the tube (wall thickness direction). The length direction of the test specimen is the axis direction of the tube. If the alloy material is an alloy sheet, the test specimen is taken from the center of the sheet thickness. The size of the test specimen is, for example, 20 mm in length, 10 mm in width, and 3 mm in thickness. A through hole with a diameter of 5 mm extending in the thickness direction is made at the longitudinal end of the test specimen. The thickness direction of the test specimen is the sheet thickness direction. The length direction of the test specimen is the rolling direction. If the alloy material is a round bar, the test specimen is taken from position R / 2. The size of the test specimen is, for example, 20 mm in length, 10 mm in width, and 3 mm in thickness. A through hole with a diameter of 5 mm and extending in the thickness direction is made at the longitudinal end of the test specimen. The thickness direction of the test specimen is the radial direction of the round bar. The length direction of the test specimen is the axial direction.

[0067] The surface of the collected test specimen is wet-polished with emery paper up to 600 grit, and then degreased with acetone. The mass of the degreased test specimen is measured and taken as the mass of the test specimen before the start of the test.

[0068] As the test solution, prepare a solution by adjusting the pH to 2.0 using H2SO4 in a 1.7 mass% NaCl aqueous solution. Place the test specimen in the autoclave while suspended from a fixture. The contact points between the fixture and the test specimen are electrically insulated with a ceramic component.

[0069] Completely replace the gas in the autoclave with air by passing N2 gas through it. Degas the test solution beforehand in a separate container by passing N2 gas through it. Inject the degassed test solution into the autoclave using a vacuum pump. Immerse the entire test specimen in the test solution. The ratio of the test specimen to the test solution should be 30 ± 10 mL / cm³. 2 The settings are configured accordingly. Then, N2 gas is passed through the liquid and gas phases in the autoclave to ensure sufficient degassing. After that, 1 atm H2S and 5 atm CO2 gas are sealed in as test gases.

[0070] The autoclave is heated to 350°C using a heater and maintained at 350°C for 336 hours. After 336 hours, the heater is turned off and the autoclave is cooled to room temperature (20±15°C). After cooling to room temperature, the test gas inside the autoclave is replaced with N2 gas. After replacing the test gas with N2 gas, the test specimen is removed.

[0071] The corrosion products are removed from the extracted test specimens. The removal of corrosion products from the test specimens is carried out, for example, according to the method specified in ASTM G31-21.

[0072] Measure the mass of the test specimen from which the corrosion products have been removed. Corrosion rate (g·m) -2 ·h -1 )(1m per hour 2The mass reduction per unit area is determined by dividing the difference between the mass of the test specimen before the start of the test and the mass of the test specimen after the test time has elapsed and the corrosion products have been removed, by the surface area of ​​the test specimen and the test time. Corrosion rate is 0.100 g·m -2 ·h -1 The following conditions will be met to determine that excellent corrosion resistance has been achieved in the next-generation geothermal environment:

[0073] [About the microstructure of austenitic alloy materials] The microstructure of the austenitic alloy material in this embodiment consists of austenite. Here, in this specification, "the microstructure consists of austenite" means that the amount of other microstructures is negligibly small.

[0074] [Shape of austenitic alloy material] The shape of the austenitic alloy material in this embodiment is not particularly limited. The austenitic alloy material may be an alloy tube, an alloy plate, or a round bar. Preferably, the austenitic alloy material in this embodiment is an alloy tube, and more preferably a seamless alloy tube.

[0075] [Manufacturing method] An example of a method for manufacturing the austenitic alloy material of this embodiment having the above-described configuration will be explained. Note that the method for manufacturing the austenitic alloy material according to this embodiment is not limited to the method described below. An example of a method for manufacturing the austenitic alloy material of this embodiment includes the following steps. (Process 1) Material preparation process (Process 2) Hot working process (Process 3) Cold working process (Step 4) Solution treatment process The following details each manufacturing process.

[0076] [Material preparation process] In the material preparation process, a molten alloy is produced by a well-known method. The method for producing the molten alloy is not particularly limited. For example, the molten alloy may be subjected to a well-known primary refining, followed by a well-known secondary refining. During refining, alloying elements for component adjustment are added to the molten alloy to produce a molten alloy that satisfies the chemical composition of Feature 1 and Feature 2.

[0077] The material is manufactured using the molten alloy. Specifically, cast slabs, blooms, or billets are produced by continuous casting using the molten alloy. Alternatively, ingots are produced by the ingot-making process using the molten alloy.

[0078] [Hot working process] In the hot working process, the material (cast slab or ingot) manufactured in the material preparation process is hot-worked to produce an intermediate alloy material. In this specification, the intermediate alloy material is a raw tube if the final product is an alloy tube, a plate-shaped alloy material if the final product is an alloy plate, and a rod-shaped alloy material extending in the axial direction if the final product is a round bar. The hot working may be hot forging, hot extrusion, or hot rolling. The method of hot working is not particularly limited and may be a well-known method.

[0079] If the intermediate alloy material is a raw pipe (seamless steel pipe), hot extrusion such as the Eugène-Séjournet method or the Erhardt-Pushbench method may be performed. Alternatively, hot rolling such as perforation rolling by the Mannesmann method may be performed. When hot extrusion is used, a round billet is manufactured by hot forging or bract rolling of the bloom or ingot. The heating temperature for hot forging or bract rolling is, for example, 1000 to 1300°C. A through hole is formed in the manufactured round billet by machining. The through hole is formed coaxially with the central axis of the round billet. A raw tube, which is an intermediate alloy material, is manufactured by hot extrusion using the round billet with the through hole formed in it. The heating temperature during hot extrusion is, for example, 1000 to 1300°C. When employing the Mannesmann process, a round billet is produced by bloc rolling of the bloom or ingot. The heating temperature during bloc rolling is, for example, 1000-1300°C. The round billet produced by bloc rolling is then cooled to room temperature. The round billet is reheated. The heating temperature is, for example, 1000 to 1300°C. After the round billet is extracted from the heating furnace, it is subjected to perforation rolling and then stretch rolling to produce a raw tube, which is an intermediate alloy material.

[0080] If the intermediate alloy material is an alloy sheet, first, the slab or ingot is heated in a heating furnace. The heating temperature is, for example, 1000 to 1300°C. The slab or ingot extracted from the heating furnace is then hot-rolled using a roughing mill and a finishing mill to produce the alloy sheet, which is the intermediate alloy material.

[0081] If the intermediate alloy material is a round bar, a billet is produced by bloc rolling of the bloom or ingot. The heating temperature for bloc rolling is, for example, 1000 to 1300°C. The billet produced by bloc rolling may be further hot-rolled in a continuous rolling mill to produce smaller billets. The produced billets are then cooled to room temperature. The billet is reheated. The heating temperature is, for example, 1000 to 1300°C. After heating, the billet is hot-rolled in a finish rolling mill to produce a round bar, which is an intermediate alloy material.

[0082] [Cold working process] In the cold working process, cold working is performed on the intermediate alloy material after hot working. If the intermediate alloy material is an alloy tube or round bar, the cold working method is, for example, cold drawing. If the intermediate alloy material is an alloy sheet, the cold working method is, for example, cold rolling. The dislocation density of the manufactured austenitic alloy is adjusted by performing a cold working process. This will be discussed later.

[0083] [Solution treatment process] In the solution treatment process, the intermediate alloy material is subjected to solution treatment as a heat treatment. Specifically, the intermediate alloy material is placed in a heat treatment furnace and heated to the solution temperature. After holding the intermediate alloy material at the solution temperature for a predetermined time, the intermediate alloy material is removed from the heat treatment furnace and cooled with water. In the heat treatment process, the solution temperature will be set to 1050-1230°C. The holding time at the solution temperature will be 1-60 minutes.

[0084] [Conditions in the manufacturing process] In the manufacturing process described above, the following conditions 1 and 2 are met. (Condition 1) The surface reduction ratio RR during the cold working process should be set to 1.0 to 60.0%. Here, the reduction ratio RR (%) is given by the following formula. Area reduction ratio RR = {1 - Cross-sectional area perpendicular to the longitudinal direction of the intermediate alloy material after cold working / Cross-sectional area perpendicular to the longitudinal direction of the intermediate alloy material before cold working} × 100 In the formula, "longitudinal direction" refers to the axial direction of the tube if the intermediate alloy material is an alloy tube, the rolling direction if it is an alloy plate, and the axial direction if it is a round bar. (Condition 2) In the solution treatment process, during the heating of the intermediate alloy material to the solution temperature, the average heating rate HR from 700°C to 900°C of the intermediate alloy material is set to 0.03 to 0.10°C / second. Conditions 1 and 2 are explained below.

[0085] [Regarding Condition 1 (Reduction ratio RR in the cold working process)] The reduction ratio RR during the cold working process affects the dislocation density of the austenitic alloy material after manufacturing. If the reduction ratio RR is less than 1.0%, even if condition 2 is met, the dislocation density of the manufactured austenitic alloy material will not be sufficient. If the reduction ratio RR is 1.0% or more, assuming that condition 2 is met, the dislocation density of the manufactured austenitic alloy material will be 1.0 × 10⁻⁶. 14 m -2 That's all. Furthermore, there is no particular upper limit to the area reduction ratio RR. For example, the upper limit of the area reduction ratio RR is 60.0%.

[0086] [Regarding Condition 2 (Heating Rate HR in the Solution Treatment Process)] Dislocations introduced into the intermediate alloy material during the cold working process are more likely to annihilate each other due to the heat applied during the solution treatment process. Therefore, it is necessary to suppress the decrease in dislocation density introduced into the intermediate alloy material during the solution treatment process.

[0087] As shown in Feature 1, the austenitic alloy material of this embodiment has a high nitrogen content. Therefore, in the temperature range where the surface temperature of the intermediate alloy material is between 700°C and 900°C, fine precipitates, which are fine nitrides and / or carbonitrides, tend to form. The fine precipitates formed in this temperature range hinder the movement of dislocations in the intermediate alloy material. The easier it is for dislocations to move, the more likely dislocation annihilation is to occur. Therefore, the fine precipitates suppress dislocation annihilation during solution treatment and suppress the decrease in dislocation density.

[0088] If the average heating rate HR of the intermediate alloy material exceeds 0.10°C / second in the temperature range from 700°C to 900°C, the average heating rate HR is too fast. In this case, the amount of fine precipitates generated is insufficient. Therefore, even if condition 1 is met, the introduced dislocations are excessively annihilated during the solution treatment. As a result, the dislocation density in the austenitic alloy material after manufacturing is insufficient.

[0089] On the other hand, if the average heating rate HR is less than 0.03°C / second, the precipitates that are formed grow coarse. These coarse precipitates do not act as a barrier to dislocation movement, and the dislocations move around them. Therefore, even in this case, the introduced dislocations are excessively annihilated during the solution treatment. As a result, the dislocation density in the austenitic alloy material after manufacturing is not sufficient.

[0090] If the average heating rate HR is 0.03 to 0.10°C / second, assuming that condition 1 is met, it is possible to suppress the excessive reduction of dislocation density introduced in the cold working process during the solution treatment. As a result, in the austenitic alloy material after manufacturing, the dislocation density is 1.0 × 10⁻⁶. 14 m -2 That's all.

[0091] The average heating rate HR (°C / sec) can be measured using well-known methods. For example, the average heating rate HR (°C / sec) can be determined from the surface temperature of the intermediate steel material measured with a non-contact thermometer and the heating time.

[0092] The austenitic alloy material of this embodiment can be manufactured through the above process. Note that the above-described method for manufacturing the austenitic alloy material is merely an example, and austenitic alloy materials satisfying features 1 to 3 may be manufactured by other methods. The austenitic alloy material of this disclosure will be described in more detail below with reference to examples. [Examples]

[0093] Austenitic alloy materials having the chemical compositions shown in Tables 1A and 1B were manufactured. Here, the F1 value is shown in the "F1" column of Table 1B. In Tables 1A and 1B, "-" means that when the significant figures of the corresponding element content are rounded to the Nth decimal place (where N is a natural number), the digit at the N+1th decimal place is rounded to 0 (zero). For example, "-" in the "Co" column means that the digit at the third decimal place is rounded to 0 (zero).

[0094] [Table 1A]

[0095] [Table 1B]

[0096] Specifically, the molten alloy for each test number was manufactured in a vacuum melting furnace. Ingots were manufactured using the ingot-forming method with the molten alloy. After heating the ingot to 1250°C, hot forging was performed to produce round billets. The round billets were cooled to room temperature. Subsequently, the round billets were reheated to 1250°C, and raw tubes were manufactured by hot extrusion based on the Eugène Séjournay method. Furthermore, cold drawing was performed on the raw tubes. The reduction ratio RR (%) in cold drawing is shown in the "Reduction Ratio RR (%)" column of Table 2.

[0097] [Table 2]

[0098] Solution treatment was performed on the raw tubes after cold drawing. The solution treatment temperature was set to 1180°C, and the holding time at the solution treatment temperature was set to 15 minutes. After the holding time, the raw tubes were water-cooled. The average heating rate HR (°C / sec) in the temperature range from 700°C to 900°C of the raw tube surface temperature is shown in the "Average heating rate HR (°C / sec)" column of Table 2. For test number 36, solution treatment was performed without cold drawing after hot forging and perforated rolling. For test number 36, the "Area reduction ratio RR (%)" column in Table 2 is shown as "-". Austenitic alloy materials (seamless alloy tubes) for each test number were manufactured using the above manufacturing process.

[0099] [Evaluation Test] The following evaluation tests were performed on each austenitic alloy material with a specific test number that was manufactured. (Test 1) Dislocation density measurement test (Test 2) Corrosion resistance test The following describes each test.

[0100] [(Test 1) Dislocation Density Measurement Test] Based on the method described in [Method for Measuring Dislocation Density] above, the dislocation density (m) of the austenitic alloy material for each test number was determined. -2The dislocation density was determined. The size of the test specimen was 20 mm wide, 20 mm long, and 2 mm thick. The thickness direction of the test specimen was in the direction of the diameter of the pipe, and the length direction of the test specimen was in the direction of the axis of the pipe. The surface of the 20 mm wide and 20 mm long section was used as the measurement surface. An X-ray diffractometer manufactured by Rigaku Corporation, product name: Rint-2500, was used. The obtained dislocation density was shown in Table 2 as "Dislocation Density (×10 14 m -2 This is shown in the ")" column.

[0101] [(Test 2) Corrosion Resistance Test] Based on the method described in the "Method for Evaluating Corrosion Resistance" above, the corrosion resistance of each test number in a next-generation geothermal environment was evaluated. The size of the test specimen was 20 mm in length, 10 mm in width, and 3 mm in thickness, with the thickness direction of the specimen being in the direction of the pipe diameter and the length direction being in the direction of the pipe axis. The obtained corrosion rate (g·m) -2 ·h -1 ) is shown in Table 2 as "Corrosion rate (g·m) -2 ·h -1 This is shown in the ")" column.

[0102] [Evaluation Results] Referring to Tables 1A, 1B, and 2, the austenitic alloy materials for test numbers 1-25 met characteristics 1-3. Therefore, the corrosion rate was 0.100 g·m. -2 ·h -1 The following results were obtained, demonstrating excellent corrosion resistance in next-generation geothermal environments.

[0103] On the other hand, in test numbers 26-30, F1 (=Mo / Ni) did not satisfy equation (1). Therefore, the corrosion rate was 0.100 g·m -2 ·h -1 It exceeded the limit, and excellent corrosion resistance could not be obtained in next-generation geothermal environments.

[0104] In test number 31, the Mo content was too low, and F1 did not satisfy equation (1). Therefore, the corrosion rate was 0.100 g·m -2 ·h -1 It exceeded the limit, and excellent corrosion resistance could not be obtained in next-generation geothermal environments.

[0105] In Test Nos. 32 and 33, the Co content was too low. Therefore, the corrosion rate was 0.100 g·m -2 ·h -1 , and excellent corrosion resistance could not be obtained in the next-generation geothermal environment.

[0106] In Test No. 34, the Cr content was too low. Therefore, the corrosion rate was 0.100 g·m -2 ·h -1 , and excellent corrosion resistance could not be obtained in the next-generation geothermal environment.

[0107] In Test No. 35, the Cu content was too high. Therefore, the corrosion rate was 0.100 g·m -2 ·h -1 , and excellent corrosion resistance could not be obtained in the next-generation geothermal environment.

[0108] In Test No. 36, cold drawing was not performed. Therefore, the dislocation density was 1.0×10 14 m -2 or less. As a result, the corrosion rate exceeded 0.100 g·m -2 ·h -1 , and excellent corrosion resistance could not be obtained in the next-generation geothermal environment.

[0109] In Test No. 37, the average temperature increase rate HR in the heat treatment step exceeded 0.10°C / sec. Therefore, the dislocation density was 1.0×10 14 m -2 or less. As a result, the corrosion rate exceeded 0.100 g·m -2 ·h -1 , and excellent corrosion resistance could not be obtained in the next-generation geothermal environment.

[0110] In Test No. 38, the average temperature increase rate HR in the heat treatment step was less than 0.03°C / sec. Therefore, the dislocation density was 1.0×10 14 m -2 or less. As a result, the corrosion rate exceeded 0.100 g·m -2 ·h -1 , and excellent corrosion resistance could not be obtained in the next-generation geothermal environment.

[0111] The embodiments of this disclosure have been described above. However, the embodiments described above are merely examples for implementing this disclosure. Therefore, this disclosure is not limited to the embodiments described above, and the embodiments described above can be modified as appropriate without departing from the spirit of this disclosure.

Claims

1. The chemical composition is expressed in mass percent. C: more than 0% and less than 0.020%, Si: 0.02-0.80%, Mn: 0.10-1.00%, P: more than 0% and less than 0.030%, S: more than 0% and less than 0.0015%, Ni: 16.00-28.00%, Co: 0.01 to 1.00%, Cr: 19.00 to less than 21.00% Mo: 3.00-9.00%, N: 0.150-0.250%, Sol. Al: 0.005–0.200%, O: more than 0% but not more than 0.0150%, Ca: 0.0005-0.0100%, Cu: 0 to 0.50%, W: 0-3.00%, and, The remainder consists of Fe and impurities. Satisfying equation (1), Dislocation density is 1.0 × 10 14 I understand -2 That's all. Austenitic alloy material. Mo / Ni≧0.20 (1) Here, the elemental symbols in equation (1) are substituted with the mass percentage content of the corresponding element.

2. The austenitic alloy material according to claim 1, The aforementioned chemical composition is expressed in mass%, Cu: 0.01-0.50%, and, Contains one or more selected from the group consisting of W: 0.01 to 3.00%, Austenitic alloy material.

3. The austenitic alloy material according to claim 1, The aforementioned chemical composition is expressed in mass%, Contains W: 0.10-3.00%, Austenitic alloy material.

4. An austenitic alloy material according to any one of claims 1 to 3, The austenitic alloy material is an alloy tube. Austenitic alloy material.

Citation Information

Patent Citations

  • High-strength and high-corrosion-resistance austenitic stainless steel and manufacturing method thereof

    CN108866419A

  • Austenitic alloy

    WO2001090432A1

  • Austenitic stainless steel pipe

    WO2013001956A1

  • Ni-Cr ALLOY MATERIAL AND OIL WELL SEAMLESS PIPE USING SAME

    WO2015072458A1

  • Alloy pipe and method for manufacturing same

    WO2021256128A1